Framework to implement business analytics: Phases and critical success factors - Laureano, Raul M. S.; Laureano, L.; Grencho, Ana Rita (Actas de la 11a Conferencia Ibérica de Sistemas y Tecnologías de Información, 2016)
Business analytics is an information system that combines different data from internal and external sources from organizations in order to help to improve the knowledge of the managers, as well as the decision making process. The competitive advantage is created by better and greater understanding of the data. It focuses on business and gathers three types of analysis: descriptive, predictive and prescriptive. This study aims to propose a framework that can guide companies in the implementation of business analytics solutions. Moreover, it aims to identify a set of critical success factors that can increase the probability of a successful implementation of the system. The framework and the critical success factors are validated through semi-structured interviews with experts in business analytics, working in the information technology industry. The results let us propose a framework with five stages and the identification of 18 critical success factors. This study allows to expand the knowledge that managers have of business analytics and its implementation, allowing the organization to create value and therefore a competitive advantage.